2019
DOI: 10.1371/journal.pgen.1007951
|View full text |Cite
|
Sign up to set email alerts
|

Searching for the causal effects of body mass index in over 300 000 participants in UK Biobank, using Mendelian randomization

Abstract: Mendelian randomization (MR) has been used to estimate the causal effect of body mass index (BMI) on particular traits thought to be affected by BMI. However, BMI may also be a modifiable, causal risk factor for outcomes where there is no prior reason to suggest that a causal effect exists. We performed a MR phenome-wide association study (MR-pheWAS) to search for the causal effects of BMI in UK Biobank (n = 334 968), using the PHESANT open-source phenome scan tool. A subset of identified associations were fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
71
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 78 publications
15
71
1
Order By: Relevance
“…Obesity traits were causally related to higher risk of T2D, in keeping with previous studies (6)(7)(8)(9)(10)(11)19,64). We could not detect a sex difference in risk of T2D from higher WHR or WHRadjBMI.…”
Section: Diabetessupporting
confidence: 89%
See 2 more Smart Citations
“…Obesity traits were causally related to higher risk of T2D, in keeping with previous studies (6)(7)(8)(9)(10)(11)19,64). We could not detect a sex difference in risk of T2D from higher WHR or WHRadjBMI.…”
Section: Diabetessupporting
confidence: 89%
“…All obesity traits increased risk of CAD in both sexes, with no difference detected in the magnitude of effect between women and men. The associations with risk of CAD in men and women combined are consistent with previous studies (4,(6)(7)(8)10,11,15,17). While observational studies have indicated that waist-related traits may be more strongly associated with cardiovascular disease in women than men, they have not been conclusive (15,17,76).…”
Section: Cardiovascular Diseasesupporting
confidence: 84%
See 1 more Smart Citation
“…Milliard et 595 al. perform a large PheWAS study to examine phenotypic associations with BMI that focus on the 596 nervousness phenotypes: the study identified known associations such as diabetes and hypertension 597 (Millard et al 2019). 598…”
Section: Phewas Of Healthy Nevada Bmi and Obesity 592mentioning
confidence: 99%
“…Mendelian randomization is an approach to assess whether a risk factor has a causal effect on an outcome based on observational data [1,2]. Mendelian randomization can exploit summarized data on genetic associations obtained from genome-wide association studies to link modifiable risk factors to disease outcomes [3,4]. However, the validity of findings from a Mendelian randomization investigation is not guaranteed.…”
Section: Introductionmentioning
confidence: 99%